2020
DOI: 10.1128/mbio.01114-20
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Efficacies of FDA-Approved Drugs against SARS-CoV-2 Infection in Ferrets

Abstract: Due to the urgent need of a therapeutic treatment for coronavirus (CoV) disease 2019 (COVID-19) patients, a number of FDA-approved/repurposed drugs have been suggested as antiviral candidates at clinics, without sufficient information. Furthermore, there have been extensive debates over antiviral candidates for their effectiveness and safety against severe acute respiratory syndrome CoV 2 (SARS-CoV-2), suggesting that rapid preclinical animal studies are required to identify potential antiviral candidates for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
177
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 183 publications
(182 citation statements)
references
References 21 publications
4
177
0
1
Order By: Relevance
“…Due to the high impact of COVID-19 and the lack of commercially available vaccines and/or NAbs, many United States (US) Food and Drug Administration (FDA)-approved or repurposed drugs are currently being suggested for the treatment of clinicallyinfected COVID-19 patients (Elfiky, 2020;Park et al, 2020b;Xu et al, 2020). As scientist and clinicians race to identify drugs for the treatment of SARS-CoV-2 infection and associated COVID-19 disease, some have been used in clinical settings with no supporting evidence of antiviral activity against SARS-CoV-2 (Reihani et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high impact of COVID-19 and the lack of commercially available vaccines and/or NAbs, many United States (US) Food and Drug Administration (FDA)-approved or repurposed drugs are currently being suggested for the treatment of clinicallyinfected COVID-19 patients (Elfiky, 2020;Park et al, 2020b;Xu et al, 2020). As scientist and clinicians race to identify drugs for the treatment of SARS-CoV-2 infection and associated COVID-19 disease, some have been used in clinical settings with no supporting evidence of antiviral activity against SARS-CoV-2 (Reihani et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Because no animal models are available that accurately re ect clinical symptoms (e.g. lung damage) of patients with severe COVID-19 [25][26][27][28][29] , ferrets, Syrian hamsters and rhesus monkeys have been used together for evaluation of SARS-COV-2 pathogenesis/transmission and to assess the e cacy of therapeutics and vaccines against COVID-19 [30][31][32][33] . In vivo challenge studies using these models has demonstrated that CT-P59 is capable of quickly decreasing virus titres, particularly improving clinical symptoms and pathological changes in ferrets.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, CQ and HCQ were considered for their therapeutic potential due to previous reports on their strong anti-SARS-CoV activity in vitro after the 2003 coronavirus outbreak [94]. Other derivatives of CQ, such as HCQ sulphate have been reported to reduce inflammation in autoimmune diseases [95]. Such information ignited interest in the potential of CQ and HCQ to treat COVID-19 ill patients.…”
Section: Repurposing the Antimalarial Drug Chloroquine For Sars-cov-2mentioning
confidence: 99%